Tsunamis and other Natural Disasters : A Nonfiction Companion to High Tide in Hawaii - Osborne, Mary Pope and Boyce, Natalie Pope (New York Random House, 2007)
Designed for younger readers, this is an informative, fact-filled guide to all kinds of natural disasters.
Include Illustration and Index
Keywords: Natural disasters -- Tsunamis